Evaluating Outcome in Perforated Peptic Ulcer by Boey and POMPP Score - Elvin Nuzulistina; Mamiek Dwi Putro; Dyah Fauziah (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Perforated peptic ulcer (PPU) is able to increase the risk of mortality and morbidity. This study used Boey and practical scoring system of mortality in patients with perforated peptic ulcer (POMPP) scoring systems to assess risk mortality of the patients. Every parameter has a value to add up 1 point in Boey and POMPP score. Methods: This observational study used medical records of PPU patients who came to Dr. Soetomo General Hospital in emergency state and being operated and treated at surgical inpatient care facility in 2016. The data were analyzed retrospectively. The sampling technique in this study was done by total sampling. Results: Most of PPU patients had the average age of 59.56 years old and 71.79% of the patients were male. Both analyzing results of Boey and POMPP scoring systems were not statistically significant to predict mortality risk of the patients. Even so, the results of Boey scoring system tended to have a positive correlation with mortality risk (0%, 37.50%, 52.94%, and 100%) with 17 patients (43.59%) had mortality. Conclusion: While Boey and POMPP score are most commonly used to predict outcome for PPU patients in Dr. Soetomo General Hospital, considerable variations in risk of mortality were shown. Therefore, both Boey and POMPP score had its own advantages and disadvantages. Further prospective research is needed to test the validity of Boey and POMPP scoring systems, thus the scoring systems can be used in daily hospital practice in patients with PPU.